How open source ate software : understand the open source movement and so much more - Haff, Gordon (ITpro collection, 2021)
Learn how free software became open source and how you can sell open source software. This book provides a historical context of how open source has thoroughly transformed how we write software, how we cooperate, how we communicate, how we organize, and, ultimately, how we think about business values. This fully updated second edition includes an entire chapter on legal considerations such as trademarks and the latest happenings in open source licensing. It also expands on open hardware trends such as RISC-V, open governance, and the difference between community projects and commercial products, especially as seen through the lens of security. You'll look at project and community examples including Linux, BSD, Apache, and Kubernetes, understand the open source development model, and how open source has influenced approaches more broadly, even within proprietary software, such as open betas. You'll also examine the flipside, the "Second Machine Age," and the challenges of open source-based business models. Today, open source serves as shorthand for much broader trends and behaviors. It's not just about a free (in all senses of the word) alternative to commercial software. It increasingly is the new commercial software. How Open Source Ate Software, second edition reveals how open source has much in common, and is often closely allied, with many other trends in business and society. You'll see how it enables projects that go beyond any individual company. That makes open source not just a story about software, but a story about almost everything. You will: Review the opportunities that open source creates and the challenges that come with them See the ways in which companies can create business models to successfully sell "free" software Understand how the open source development model works from creating communities to selling commercial products Examine the important issues associated with open source project and product governance and licensing Look at how open source principles can apply more broadly to DevOps and other organizational practices